(3JgPjH GdCNdGbs - (3CHh RcQjG, jMji Hf YOj Hf MejO Hf RcQjG, J (B364(3g`s
(3ChdgG (B:s
(3GYde Cf GdEfSGf ef Hjf SGFQ GdMjhGf Ph acQ hJejjR hgh HPG jMH ef GdCehQ CaVdgG hef GdeQGJH CTQagGs
(3BNQgG (B:s
(3hLejd GdPcQ eNdOG abO CJjfG Ydi UaI GdEfSGf GdJGe GdLGeY deMGSf GdCNdGb(B... (3ef fXQ aj gPG Gdbhd hJUaMg(B... (3hgPG Mjf fNJe Gdbhd aj JgPjH GdCNdGbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B8(3, (B156s
(3GdCYdGe(B: (3L(B8(3, (B156s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs